Exposure-based treatments for childhood abuse-related post-traumatic stress disorder in adults: a health-economic evaluation. Issue 1 (31st December 2023) - Kullberg, Marie-Louise J.; Schoorl, Maartje; Oprel, Danielle A. C.; Hoeboer, Chris M.; Smit, Filip; van der Does, Willem; de Kleine, Rianne A.; van Minnen, Agnes; van den Hout, Wilbert
ABSTRACT: Background: Prolonged exposure (PE) is an effective treatment for post-traumatic stress disorder (PTSD). Objective: This study aimed to analyse the cost-effectiveness of three exposure-based treatments in patients with childhood abuse-related PTSD. Method: A net–benefit analysis was conducted alongside a pragmatic randomized controlled trial with participants ( N = 149) randomized to three conditions: PE ( n = 48), intensified PE (i-PE, n = 51), and phase-based PE [Skills Training in Affective and Interpersonal Regulation (STAIR) + PE, n = 50]. Assessments took place at baseline (T0), post-treatment (T3), 6 month follow-up (T4), and 12 month follow-up (T5). Costs stemming from healthcare utilization and productivity losses were estimated using the Trimbos/iMTA questionnaire for Costs associated with Psychiatric Illness. Quality-adjusted life-years (QALYs) were based on the 5-level EuroQoL 5 Dimensions (EQ-5D-5L) using the Dutch tariff. Missing values of costs and utilities were multiply imputed. To compare i-PE to PE and STAIR + PE to PE, pair-wise unequal-variance t -tests were conducted. Net–benefit analysis was used to relate costs to QALYs and to draw acceptability curves. Results: Intervention costs did not differ across the three treatment conditions. Total medical costs, productivity losses, total societal costs, and EQ-5D-5L-based QALYs did not differ between treatment conditions either (all p > .10). At the relevant €50, 000/QALY threshold, the probability of one treatment being more cost-effective than another was 32%, 28%, and 40% for PE, i-PE, and STAIR-PE, respectively. Conclusion: Three equally effective treatments were compared and no differences in cost-effectiveness between treatments were found. Therefore, we advocate the implementation and adoption of any of the treatments and endorse shared decision making. HIGHLIGHTS: This is the first study to compare cost-effectiveness of three exposure-based treatments in patients with CA-PTSD alongside a randomized controlled clinical trial ( N = 149). The three exposure-based treatments did not differ in terms of outcomes and costs. Findings underline that any of these treatments can be implemented, and we endorse shared decision making to meet patient treatment preference.